FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN PROPERTY, REAL ESTATE AND BUILDING YANG TERDAFTAR DI BEI TAHUN 2013-2015 - Selano, Elysabet Christy Diandra; Tedjasuksmana, Budianto; Wardani, Rr. Puruwita (Jurnal Akuntansi Kontemporer, 2017)
This study aimed to analyze the factors that influence the tendency of fraudulent financial statement with analysis of the fraud triangle. The samples used by the company of property, real estate and building construction which listed at Indonesia Stock Exchange in the 2013-2015 period. The result showed that the variable of financial stability as measured by the ratio of asset change and variable of external pressure as measured by leverage did not find the influence on tendency of fraudulent financial statement. While, variables of financial target as measured by ROA, nature of industry as measured by inventory, ineffective monitoring as measured by BDOUT and rationalization as measured by audit report show that influence on tendency of fraudu-lent financial statement.